Nano-engineered hierarchical porous silicas for enhanced catalytic efficiency in the liquid phase. Issue 18 (30th August 2018) - Zaki, A.; Wastiaux, M.; Casale, S.; Mussi, A.; Dhenin, J. F.; Lancelot, C.; Dacquin, J. P.; Granger, P.
Abstract : By tailoring the pore properties (size, morphology and orientation) of hierarchical catalysts, we show experimentally the importance of active phase accessibility on catalytic efficiency. Abstract : By tailoring the pore properties (size, morphology and orientation) of hierarchical catalysts, we show experimentally the importance of active phase accessibility on catalytic efficiency. This finding likely contributes to a better rationalisation of the structure sensitivity of the nitrite hydrogenation reaction, through the enhancement of mass transfer phenomena.